2022
DOI: 10.1186/s12936-022-04099-5
|View full text |Cite
|
Sign up to set email alerts
|

Sub-national tailoring of malaria interventions in Mainland Tanzania: simulation of the impact of strata-specific intervention combinations using modelling

Abstract: Background To accelerate progress against malaria in high burden countries, a strategic reorientation of resources at the sub-national level is needed. This paper describes how mathematical modelling was used in mainland Tanzania to support the strategic revision that followed the mid-term review of the 2015–2020 national malaria strategic plan (NMSP) and the epidemiological risk stratification at the council level in 2018. Methods Intervention mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 78 publications
1
10
0
Order By: Relevance
“…In this study, RDT prevalence rates ranged from 20.0% to 43.6%, and these results from this community population shows evidence for the high P. falciparum transmission in these northwestern and southeastern border regions of Tanzania. These high-transmission regions have been confirmed by recent reports [5,31,32], and similar findings by NIMR were the impetus for selection of villages within these border regions for this 2017 survey [17]. No correlation was seen between any RDT LOD estimates (at the 50, 75, 90, or 95% probability levels of RDT positivity) and the observed percentage of the study population infected with P. falciparum at the time of enrollment.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, RDT prevalence rates ranged from 20.0% to 43.6%, and these results from this community population shows evidence for the high P. falciparum transmission in these northwestern and southeastern border regions of Tanzania. These high-transmission regions have been confirmed by recent reports [5,31,32], and similar findings by NIMR were the impetus for selection of villages within these border regions for this 2017 survey [17]. No correlation was seen between any RDT LOD estimates (at the 50, 75, 90, or 95% probability levels of RDT positivity) and the observed percentage of the study population infected with P. falciparum at the time of enrollment.…”
Section: Discussionsupporting
confidence: 85%
“…Modelling can account for multiple data sources (seasonality, burden, planned interventions, coverage) to determine which strategy is likely to save most lives. Previous works using mathematical modelling for strategic planning focused on showing the likely impact of already determined combinations of interventions to advocate for funding [14, 30]. This analysis shows that country-specific models can also be used to guide the development of strategies by answering to specific questions of interest for decision makers.…”
Section: Discussionmentioning
confidence: 99%
“…Modelling can account for multiple data sources (seasonality, burden, planned interventions, coverage) to determine which strategy is likely to save most lives. Previous works using mathematical modelling for strategic planning focused on showing the likely impact of already determined combinations of interventions to advocate for funding [14,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent reports on malaria status in Tanzania showed that malaria is still the leading cause of morbidity and mortality, with notifications of infection transmission resurgence in some areas (Chacky et al 2018 ; Finda et al 2018 ; Insehngoma et al 2018 ; Mapua et al 2022 ; Mitchell et al 2022 ; WHO 2021 ). Kigoma Region is one area in Tanzania contributing to the observed high burden of malaria, as it has a very high transmission risk (Runge et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%